Clinical implication of ticagrelor monotherapy in patients with small vessel coronary artery disease: results from the TICO randomized trial - Cho, Jae Young; Joo, Donghyeon; Yun, Kyeong Ho; Kim, Byeong-Keuk; Hong, Myeong-Ki; Jang, Yangsoo; Oh, Seok Kyu (Frontiers in Cardiovascular Medicine, 2023)
Background The aim of this study was to evaluate the efficacy and safety of ticagrelor monotherapy in patients with small vessel disease compared with ticagrelor-based DAPT within the Ticagrelor Monotherapy after 3 Months in the Patients Treated with New Generation Sirolimus Eluting Stent for Acute Coronary Syndrome (TICO) trial population. Methods Reference vessel diameter ≤2.5 mm was considered as small vessel disease. We conducted a comparison of the incidence of target lesion failure (TLF) and Bleeding Academic Research Consortium (BARC) type 3 or 5 bleeding. TLF was defined as a composite of cardiac death, target lesion myocardial infarction, stent thrombosis, and target lesion revascularization. Results 652 patients among 3,056 TICO population (21.3%) had small vessel disease. Patients with small vessel disease showed a higher rate of TLF compared to those without small vessel disease (2.9% vs. 1.0%, log-rank p < 0.001). The presence of small vessel disease emerged as an independent predictor for 1-year TLF (HR 2.84, 95% CI 1.54–5.25), while it did not show a significant association with bleeding complications. The 12-month TLF rate was 1.6% for ticagrelor monotherapy after 3-month DAPT, and 4.2% for ticagrelor-based 12-month DAPT (p = 0.059) in patients with small vessel disease (HR 0.38, 95% CI 0.14–1.04, p for interaction = 0.261). The incidence of BARC type 3 or 5 bleeding rate 2.5% for ticagrelor monotherapy after 3-month DAPT, and 5.6% for ticagrelor-based 12-month DAPT (p = 0.052) in patients with small vessel disease (HR 0.44, 95% CI 0.19–1.01, p for interaction = 0.322). In the 3-month landmark analysis, ticagrelor monotherapy significantly reduced BARC type 3 or 5 bleeding in patients with small vessel disease (HR 0.09, 95% CI 0.01–0.69, log-rank p = 0.005) while demonstrating a similar incidence of TLF compared to ticagrelor based 12-month DAPT during the 3–12 months period. Conclusions There are no significant interactions between the antiplatelet strategy regarding the 12-month incidence of ischemic and bleeding complications. Ticagrelor monotherapy demonstrated a reduction in bleeding complications after a 3-month period of DAPT without increasing the rate of TLF, when compared to ticagrelor-based 12-month DAPT, specifically in patients with small vessel disease. Clinical Trial Registration: www.ClinicalTrials.gov, identifier, NCT02494895.